LGR5 controls extracellular matrix production by stem cells in the developing intestine. (28th May 2020) - Fernandez Vallone, Valeria; Leprovots, Morgane; Ribatallada‐Soriano, Didac; Gerbier, Romain; Lefort, Anne; Libert, Frédérick; Vassart, Gilbert; Garcia, Marie‐Isabelle
Abstract: The Lgr5 receptor is a marker of intestinal stem cells (ISCs) that regulates Wnt/b‐catenin signaling. In this study, phenotype analysis of knockin/knockout Lgr5‐eGFP‐IRES‐Cre and Lgr5‐DTReGFP embryos reveals that Lgr5 deficiency during Wnt‐mediated cytodifferentiation results in amplification of ISCs and early differentiation into Paneth cells, which can be counteracted by in utero treatment with the Wnt inhibitor LGK974. Conditional ablation of Lgr5 postnatally, but not in adults, alters stem cell fate toward the Paneth lineage. Together, these in vivo studies suggest that Lgr5 is part of a feedback loop to adjust the Wnt tone in ISCs. Moreover, transcriptome analyses reveal that Lgr5 controls fetal ISC maturation associated with acquisition of a definitive stable epithelial phenotype, as well as the capacity of ISCs to generate their own extracellular matrix. Finally, using the ex vivo culture system, evidences are provided that Lgr5 antagonizes the Rspondin 2‐Wnt‐mediated response in ISCs in organoids, revealing a sophisticated regulatory process for Wnt signaling in ISCs. Synopsis: The stem cell marker Lgr5 is part of a feedback loop allowing fine‐tuning of Wnt signaling in intestinal stem cells during late fetal and postnatal development. Its interaction with the Rspondin 2 ligand modulates epithelial extracellular matrix production. Lgr5 deficiency during Wnt‐mediated cytodifferentiation results in the amplification of the stem cell pool. Lgr5 deficiency also increases early Paneth cell differentiation during mouse intestinal development. Intestinal Lgr5 + stem cell maturation is associated with progressive reduction of matrisome components. The Rspo2/Lgr5 interaction in intestinal stem cells fine‐tunes Wnt signalling and ECM production in the epithelium. Abstract : The stem cell marker Lgr5 is part of a feedback loop allowing fine‐tuning of Wnt signaling in intestinal stem cells during late fetal and postnatal development. Its interaction with the Rspondin 2 ligand modulates epithelial extracellular matrix production.